Reducing Interprofessional Conflicts in Order to Facilitate Better Rural Care: A Report From a 2018 Rural Surgical Network Invitational Meeting - Pelletier, Hayley (Université d'Ottawa | University of Ottawa, 2018)
An invitational meeting organized by the Centre for Rural Health Research convened to facilitate respectful dialogue with general surgeons in British Columbia; the objective was to clearly understand concerns and address questions around rural family physicians with enhanced surgical skills (FPESS). In particular, the meeting focused on interprofessional challenges that hinder the adoption of a net-work model between general surgeons and FPESS. This report summarizes the findings (n = 5) and recommendations (n = 8) made during the meeting. The meeting underscored the need for more thoughtful discussions to develop inter-professional trust and support between general surgeons and FPESS through an integrated health care system and proper networks.
Keywords: rural; rural health services; FPESS; general surgeon; British Columbia; network